Dialysis‐related Amyloidosis: Is It Gone or Should It Be?. Issue 3 (6th March 2017) - Labriola, Laura; Jadoul, Michel
Abstract: The prevalence and severity of dialysis‐related amyloidosis (DRA) appear to have decreased significantly over the last two decades, although recent, large‐scale epidemiological studies show that DRA continues to occur. Recent experimental findings have documented a direct cellular toxicity of β2microglobulin (β2m) fibrils but the mechanisms of β2m fibrillogenesis remain incompletely understood. Although a high plasma concentration of β2m is still considered as a prerequisite for developing DRA, other factors have been clearly incriminated such as older age at dialysis onset and longer dialysis vintage, or suspected effects such as proinflammatory effects of bioincompatible dialysis techniques. Improved dialysis technology has definitely played a role in delaying the onset of the disease, although the respective contributions of high‐flux biocompatible membranes, use of convective mode, and ultrapure dialysate remain imperfectly defined. Importantly, DRA still does exist and no current dialytic modality seems able to fully prevent it. Awaiting further progress in the understanding of DRA pathogenesis, the use of biocompatible high‐flux membranes and ultrapure dialysate is strongly recommended in order to minimize or delay its onset. Convective regimens may provide an additional benefit.